1993
DOI: 10.1029/93ja01609
|View full text |Cite
|
Sign up to set email alerts
|

Observations of an intermediate shock in interplanetary space

Abstract: An interplanetary intermediate shock is identified from the bulk velocity, number density, and temperature of the solar wind protons and tl•e three components of the interplanetary magnetic field observed by Voyager 1 on May 1 (day 122), 1980, when the spacecraft was at a distance of about 9 AU froln the Sun. It is shown by a best fit procedure that the ineasured plasma and magnetic field on both sides of the discontinuity satisfy the Rankine-Hugoniot relations for a magnetohydrodynamic (MHD) intermediate shoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 21 publications
4
32
0
Order By: Relevance
“…However, Wu (1987) showed that, via simulation of a set of resistive MHD equations, that the intermediate shock can be stable in some situations. In addition, Chao et al (1993) identified an intermediate shock near 9 AU from the Voyager 1 plasma and magnetic field data. Whang (1987) suggested that the decrease in the Alfvén speed at increasing heliocentric distance causes the normal Alfvén Mach number of a forward slow shock to become greater than 1, and the shock should eventually evolve from a slow shock into a fast shock.…”
Section: Introductionmentioning
confidence: 99%
“…However, Wu (1987) showed that, via simulation of a set of resistive MHD equations, that the intermediate shock can be stable in some situations. In addition, Chao et al (1993) identified an intermediate shock near 9 AU from the Voyager 1 plasma and magnetic field data. Whang (1987) suggested that the decrease in the Alfvén speed at increasing heliocentric distance causes the normal Alfvén Mach number of a forward slow shock to become greater than 1, and the shock should eventually evolve from a slow shock into a fast shock.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past more than four decades, there have been a large number of numerical investigations for ISs. In spite of evolutionary conditions, ISs are commonly observed to be stable shocks in numerical simulations (e.g., Wu 1987;Wu & Hada 1991;Takahashi et al 2013Takahashi et al , 2014, and two interplanetary ISs have been observed and reported (Chao et al 1993;Feng & Wang 2008). However, both ISs were identified through fitting the R-H relations based on one spacecraft observation.…”
Section: Discussionmentioning
confidence: 99%
“…However, observations of ISs are very rare; to our knowledge, only two cases have been reported. One is a  2 4 type IS, which was observed in 1980 when Voyager 1 was approximately at 9 au from the Sun (Chao et al 1993); the other is a  2 3 type IS, which was detected at 4.5 au by Voyager 2 in 1979 (Feng & Wang 2008). Both ISs were observed far away from the Sun, and they were detected only by one spacecraft, so they were identified based only on fitting the R-H relations.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally ͑Akhiezer, Liubarski, and Polovin, 9 Germain, 10 Jeffrey and Taniuti 11 ͒, this failure of the test of evolutionarity was used to rule out the physical reality of intermediate shocks. However, after Wu 13 showed intermediate shocks to arise in numerical solutions of the dissipative MHD equations, a flurry of numerical and observational papers appeared on the structure and formation of intermediate shocks, [25][26][27][28][29] on their astrophysical implications, 30,31 on their relationship with magnetic reconnection, 32,33 on their significance for the Riemann problem, [34][35][36] on their occurrence in bow-shock flows, 37 and their possible breakup. 38 As mentioned in the Introduction, Falle and Komissarov 16 presented arguments to stick to the traditional view point.…”
Section: -17mentioning
confidence: 99%